2016
DOI: 10.1038/srep28048
|View full text |Cite
|
Sign up to set email alerts
|

Integrated network-diversity analyses suggest suppressive effect of Hodgkin’s lymphoma and slightly relieving effect of chemotherapy on human milk microbiome

Abstract: We aim to investigate the effects of Hodgkin’s lymphoma and the chemotherapy for treating the disease on the human milk microbiome through integrated network and community diversity analyses. Our analyses suggest that Hodgkin’s lymphoma seems to have a suppressing effect on the milk microbiome by lowering the milk microbial community diversity, as measured by the Hill numbers profiles. Although the diversity analysis did not reveal an effect of chemotherapy on community diversity, bacterial species interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…Changes in the metabolic profile of milk, characterized by a decrease of inositol and docosahexaenoic, were also observed (Urbaniak et al, 2014b). The second study provided contradictory results since no negative effect of chemotherapy on community diversity was found (Ma et al, 2016).…”
Section: Maternal Treatments (Antibiotics Probiotics Prebiotics Anmentioning
confidence: 95%
“…Changes in the metabolic profile of milk, characterized by a decrease of inositol and docosahexaenoic, were also observed (Urbaniak et al, 2014b). The second study provided contradictory results since no negative effect of chemotherapy on community diversity was found (Ma et al, 2016).…”
Section: Maternal Treatments (Antibiotics Probiotics Prebiotics Anmentioning
confidence: 95%
“…The robust microbiotas, able to regain their original function upon disturbances, should be identified. The proposed networking approach on the breast milk dataset was recently employed for the geographically distinct healthy cohort (Ma et al, 2015 ) and was also applied (Ma et al, 2016 ) in the preliminary comparative analysis of Hodgkin's lymphoma milk microbiome after drug administration. Moreover, the authors suggested the metabolites-microbial species networks to be very useful in identifying the active bacterial taxa really involved in the milk microbial communities conferred to infants.…”
mentioning
confidence: 99%
“…The network analysis approach. We adopted standard approach for correlation network analysis to construct and analyze the human oral microbiome network with the 16s-rRNA datasets originally reported by Zaura et al 24,[36][37][38][39] . To reduce the noise effect of the OTUs with extremely low abundance and potentially spurious OTU reads, we filtered out the OTUs whose total reads in all 29 samples were less than 30, i.e., approximately one read per sample, equivalent to removing the so-called singleton, which is a common practice in ecological analysis.…”
Section: Methodsmentioning
confidence: 99%